Analisis Break Even Point Sebagai Alat Perencanaan Laba Pada Danbo Dramabox DC. Collection Di Desa Tribungan Kecamatan Mangaran Kabupaten Situbondo - Karnadi Karnadi; Atika Dwi Hermawati (Fakultas Ekonomi Universitas Panca Marga, 2019)
This study aims to (1) To find out how many break-even points in 2015-2017 (2) To find out how many sales plans are in 2018 and 2019 (3) To find out how many minimum sales must be achieved so that the company does not lose (4) To find out how much profit planning in 2018 and 2019. The method used in this study is a quantitative method. The results of the study were the break-even point for 2015 in the first semester of Rp. 29,103,640 with a margin of safety of 28%, semester II of Rp. 32,577,057 with a margin of safety of 31%. In 2016 the third semester amounted to Rp. 35,151,516 with a margin of safety of 35%, semester IV of Rp. 36,776,275 with a margin of safety of 39%. The year 2017 semester V of Rp. 43,376,025 with a margin of safety of 35%, semester VI of Rp. 42.79.674 with a margin of safety of 49%. The year 2018 targets profit in the VII semester, which is Rp. 16,634,975, semester VIII which is Rp. 18,902,975 and in 2019 in the IX semester that is Rp. 23,892,575, semester X which is Rp. 26,378,975. Keywords: Break Even Point, Profit Planning Tool, Danbo Dramabox